DEVELOPMENT OF METHODS OF INFORMATION MODELS SPECIFICATION BY MEANS OF THE EVENT TABLES LANGUAGE - Кулешова, Ольга Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The methodology of the event tables language implementation for the specification and simulation of complex systems is presented.